2018
DOI: 10.1152/ajprenal.00639.2017
|View full text |Cite
|
Sign up to set email alerts
|

Vascular type 1 angiotensin receptors control blood pressure by augmenting peripheral vascular resistance in female mice

Abstract: Angiotensin II (ANG II) is a major mediator of hypertension pathogenesis. In addition, there are well-documented differences in expression of the renin-angiotensin system (RAS) components and ANG II responses between males and females, which may explain sex differences in blood pressure (BP) and hypertension epidemiology. We previously showed that type 1A angiotensin (AT) receptors in vascular smooth muscle cells (VSMCs) play a critical role in BP regulation and hypertension pathogenesis, but these studies wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 59 publications
2
16
0
Order By: Relevance
“…In previous studies, we confirmed an important direct contribution of AT 1 receptors in VSMCs to blood pressure control and hypertension pathogenesis using mice with cell-specific deletion of AT 1A receptors, the major murine AT 1 receptor isoform (20), from smooth muscle (SMKO mice) (21,22). These SMKO mice lacking AT 1A receptors in VSMCs have lower baseline blood pressures, preserved renal blood flow (RBF), and attenuated hypertensive responses to chronic ANG II administration (21,22). Furthermore, they exhibit enhanced natriuresis during chronic ANG II infusion, which we posited was a key mechanism in their resistance to hypertension (21).…”
Section: Introductionsupporting
confidence: 71%
See 4 more Smart Citations
“…In previous studies, we confirmed an important direct contribution of AT 1 receptors in VSMCs to blood pressure control and hypertension pathogenesis using mice with cell-specific deletion of AT 1A receptors, the major murine AT 1 receptor isoform (20), from smooth muscle (SMKO mice) (21,22). These SMKO mice lacking AT 1A receptors in VSMCs have lower baseline blood pressures, preserved renal blood flow (RBF), and attenuated hypertensive responses to chronic ANG II administration (21,22). Furthermore, they exhibit enhanced natriuresis during chronic ANG II infusion, which we posited was a key mechanism in their resistance to hypertension (21).…”
Section: Introductionsupporting
confidence: 71%
“…6). In previous studies, we found that SMKO mice had attenuated hypertension, exaggerated natriuresis, and diminished cardiac hypertrophy in response to chronic ANG II infusion (21,22,40). Furthermore, we have reported in this model (40) and others (9) that the magnitude of cardiac hypertrophy is directly correlated with the extent of blood pressure elevation in ANG II hypertension.…”
Section: Altered Profile Of Kidney Epithelial Transporters In Control Mice During Ang II Hypertensionsupporting
confidence: 52%
See 3 more Smart Citations